Effect of Acid on Natural Zeolite Dealumination on Indigo Carmine Adsorption Capability - Nanik Sulistyowati; Sriyanti Sriyanti; Adi Darmawan (Jurnal Kimia Sains dan Aplikasi, 2018)
Modifying natural zeolite with dealumination using H2SO4 and HCl, and its application to adsorb indigo carmine has been performed. Dealumination was carried out by reacting a natural zeolite with a mixture of KMnO4-H2SO4 and a mixture of KMnO4-HCl then refluxed for 5 hours followed by washing with demineralized water until a neutral pH was obtained and dried for 12 hours at 80°C. Dealuminated zeolites were then characterized by XRD, FTIR and Si/Al ratio measurements. Dealuminated zeolite was then used to adsorb indigo carmine in a batch-shaker system for 30 min with concentration variation XRD diffraction shows that natural zeolite and dealuminated zeolite contain modernit minerals. Dealumination increased the Si/Al ratio from 0.935 to 2.075 and 7.912 which meant that dealumination was successful. The indigo carmine adsorption result showed that zeolite adsorption capacity II> zeolite I> natural zeolite. FTIR data showed that there was no change of zeolite structure before and after adsorption